An ethnographic exploration of the effectiveness of formal leadership development programmes within the context of the UK and New Zealand public sectors - Smolovic Jones, Owain (Cranfield University, 2011)
This thesis examines whether formal leadership development programmes can improve the delivery of leadership within the context of four specific sectors. These are UK local government, the UK Fire and Rescue Service, the UK armed services and the New Zealand public services. Theories of leadership development are linked to theories of leadership, with the conclusion drawn that leadership development perspectives are influenced and follow principles of leadership theory. Two broad foci of leadership development are identified, ‘individual’ and ‘collective’. Within these, four particular ‘schools’ of leadership development are discussed in order to establish a guide to consider what may constitute an effective leadership development process - behavioural, authentic, coalition and experiential. These four theoretical models are presented with a view to further testing in the field. It is suggested that a research method which values and gives voice to the subjective constructions of actors in the process of leadership development should be adopted. The case is made for an ethnographic method – specifically citing its capacity for rich, deep descriptions, data capture over an extended period of time and within a range of settings. Results are presented offering support for three of the four models presented – authentic, coalition and experiential, but not for behavioural leadership development. The case is made that leadership development programmes, from the perspective of participants and their colleagues, do improve the practice of leadership – at least to a degree. It is stated, however, that it is a basic principle of ethnography that such a finding will always be bound by the context within which the data was gathered. Furthermore, it is noted that there was evidence present of more than one of the models presented co-existing within leadership development programmes. In fact, where this happened, participants believed a more dramatic improvement had taken place. With this in mind, a synthesis model is suggested, which seeks to view leadership development as a sensemaking process, rather than as a series of separate events.